Control of Hydraulic Transients in the Water Piping System in Badra – Pumping Station No. 5 - Chaichan, Miqdam Tariq; Al-Zubaidi, Dina Saadi Muneam (Nahrain University College of Engineering Journal, 2017)
In this paper, the surge tank utilization method was used to prevent the water hammer. The study was conducted on a practical problem at pipelines and pumping station of Badra – pumping station No. 5, which is possessed to Iraqi General Company for Execution and Irrigation. For this purpose, Surge2012 transient analysis software was used to achieve the best design and checking parameters.The study recommends installing 2x14m3 closed surge tanks near to lifting station. The outlet/inlet nozzle has to be of 300 mm diameter. The initial air volume must be 5 m3 for each one. All these parameters must be achieved to maintain a positive and negative pressure waves in pipe network system within accepted values.